2015
DOI: 10.1155/2015/180187
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and pH Responsive Microfibers for Controllable and Variable Ibuprofen Delivery

Abstract: Electrospun microfibers (MFs) composed of pH and temperature responsive polymers can be used for controllable and variable delivery of ibuprofen. First, electrospinning technique was employed to prepare poly( -caprolactone) (PCL) and poly(Nisopropylacrylamide-co-methacrylic acid) (pNIPAM-co-MAA) MFs containing ibuprofen. It was found that drug release rates from PCL MFs cannot be significantly varied by either temperature (22-40 ∘ C) or pH values (1.7-7.4). In contrast, the ibuprofen (IP) diffusion rates from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…In this study, pure PDS fibers were fabricated as a control. It was noticed that while the highest 95 PCL/pNIPAM-co-MAA Ibuprofen Anti-inflammatory drug action pNIPAM-co-MAA fibers were 1608 nm, PCL was 1237 nm Abidian et al 96 fiber diameters were observed in pure PDS fibers at 1,158 ± 402 nm, the lowest diameters were observed in 25 wt % CIP incorporated fibers. Furthermore, fibers with higher weight percentage of incorporated therapeutic molecules released drugs for longer than others.…”
Section: Acs Biomaterials Science and Engineeringmentioning
confidence: 97%
See 2 more Smart Citations
“…In this study, pure PDS fibers were fabricated as a control. It was noticed that while the highest 95 PCL/pNIPAM-co-MAA Ibuprofen Anti-inflammatory drug action pNIPAM-co-MAA fibers were 1608 nm, PCL was 1237 nm Abidian et al 96 fiber diameters were observed in pure PDS fibers at 1,158 ± 402 nm, the lowest diameters were observed in 25 wt % CIP incorporated fibers. Furthermore, fibers with higher weight percentage of incorporated therapeutic molecules released drugs for longer than others.…”
Section: Acs Biomaterials Science and Engineeringmentioning
confidence: 97%
“…Tran et al incorporated two types of ibuprofen (an antiinflammatory drug) into the microfibers using an electrospinning approach. 95 One type of microfibers were fabricated from polycaprolactone (PCL), while the other type was composed of poly(N-isopropylacrylamide-co-methacrylic acid) (pNIPAM-co-MAA). The average diameter of PCL fibers was 1237 nm, whereas that of pNIPAM-co-MAA fibers was 1608 nm.…”
Section: Miscellaneous Innovations In Electrospun Fiber Based Drug Dementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, these authors fabricated NFs with a core/shell structure made of ES100 for the shell and Eudragit L100 (EL100) for the core to allow the controlled release at certain pH conditions, and controlled this release using the cover thickness [57]. Tran et al [58] introduced ibuprofen into pH- and thermo-responsive polymers for controlled drug delivery investigations. Ibuprofen was initially mixed with a polymeric solution of PCL as the control experiment and also into poly(Nisopropylacrylamide-co-methacrylic acid) (pNIPAM-co-MAA) to fabricate stimuli-responsive NFs by blend electrospinning.…”
Section: Electrospun Nanofibers For Drug Delivery Applicationmentioning
confidence: 99%
“…Patterning of the actuating elements within the device structure can produce complex shape transformations through a series of discrete manipulations 17,20 . To date, these demonstrated multi-transforming gel actuated structures need complicated fabrication methods such as electrospinning with controlled fiber orientation 23,25 and stripe polymerization using photo-masking techniques 19,20,23,24 . In the present study, we demonstrate control of the gel actuation by incorporating variants of PNIPAM to give a range of LCSTs within the same device.…”
Section: Introductionmentioning
confidence: 99%